2012
DOI: 10.1073/pnas.1111573109
|View full text |Cite
|
Sign up to set email alerts
|

Role of retroviral restriction factors in the interferon-α–mediated suppression of HIV-1 in vivo

Abstract: The antiviral potency of the cytokine IFN-α has been long appreciated but remains poorly understood. A number of studies have suggested that induction of the apolipoprotein B mRNA editing enzyme, catalytic polypeptide 3 (APOBEC3) and bone marrow stromal cell antigen 2 (BST-2/tetherin/CD317) retroviral restriction factors underlies the IFN-α-mediated suppression of HIV-1 replication in vitro. We sought to characterize the as-yet-undefined relationship between IFN-α treatment, retroviral restriction factors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 57 publications
9
116
0
Order By: Relevance
“…Also upregulated by IFN-␣14 was tetherin, which inhibits the release of virions from infected cell membranes and is antagonized by HIV-1 Vpu (62). The extent of tetherin induction has been shown to correlate with reduced viral loads in HCV/HIV-1-coinfected patients treated with ribavirin and IFN-␣2 (16). In addition to its direct antiviral effects, tetherin has also been associated with improved antiretroviral NK cell responses (63,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also upregulated by IFN-␣14 was tetherin, which inhibits the release of virions from infected cell membranes and is antagonized by HIV-1 Vpu (62). The extent of tetherin induction has been shown to correlate with reduced viral loads in HCV/HIV-1-coinfected patients treated with ribavirin and IFN-␣2 (16). In addition to its direct antiviral effects, tetherin has also been associated with improved antiretroviral NK cell responses (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␣ is rapidly induced and secreted by cells to limit virus replication through numerous and varied mechanisms, including the induction of intrinsic restriction factors (15)(16)(17)(18) and the activation of innate and adaptive immune responders. In vitro studies with pDCs, which are the primary producers of IFN-␣, indicated that the predominant IFN-␣ subtypes produced by pDCs in response to HIV-1 (IFN-␣1, -2, and -5) have only weak anti-HIV-1 activities (14).…”
mentioning
confidence: 99%
“…During acute infection, pDCs may be a critical antiviral agent. IFN-a has long been known to block HIV-1 replication in vitro and in vivo [74][75][76][77]. Several studies performed during the past few years have identified a number of IFN-stimulated cellular factors (e.g.…”
Section: Insights Into Immune Responses Conferring Spontaneous Contromentioning
confidence: 99%
“…Several studies performed during the past few years have identified a number of IFN-stimulated cellular factors (e.g. MX2, BST-2/tetherin, TRIM5a, APOBEC3G and SAMHD1) that can restrict retroviral replication [74,[78][79][80][81]. During acute infection, transmitted founder viruses (HIV strains that succeed in establishing a persistent infection [82]) are more resistant to IFN-I than chronic-phase HIV strains [83,84].…”
Section: Insights Into Immune Responses Conferring Spontaneous Contromentioning
confidence: 99%
See 1 more Smart Citation